1991
DOI: 10.1093/ndt/6.7.480
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Alanine Aminotransferase Activity Reflects Exposure to Hepatitis C Virus in Haemodialysis Patients

Abstract: Prospective studies have shown that the annual incidence of non-A, non-B (NANB) hepatitis may be high in haemodialysis patients. To assess whether hepatitis C virus (HCV), the major causative agent of post-transfusion and community-acquired NANB hepatitis, has a role in the pathogenesis of liver disease in dialysed patients, we have studied the prevalence and significance of antibodies to HCV in a cohort of patients with end-stage renal disease on chronic haemodialysis treatment. Seventy-four (30%) had circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
22
1
2

Year Published

1992
1992
1999
1999

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 9 publications
3
22
1
2
Order By: Relevance
“…Statistically significant associations with the anti-HCV carrier status were: duration of dialysis treat ment, blood transfusions and the retrospective finding of abnormally elevated ALT on at least I occasion (table 1). Although these associations were also found using the 1st generation assay [3], this study revealed that duration of dialysis was an independent risk factor of acquiring HCV infection, irrespective of blood transfusions (table 1). Thirty-seven anti-HCV-positive patients were also tested by 2nd generation recombinant immunoblot assay (RI BA).…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…Statistically significant associations with the anti-HCV carrier status were: duration of dialysis treat ment, blood transfusions and the retrospective finding of abnormally elevated ALT on at least I occasion (table 1). Although these associations were also found using the 1st generation assay [3], this study revealed that duration of dialysis was an independent risk factor of acquiring HCV infection, irrespective of blood transfusions (table 1). Thirty-seven anti-HCV-positive patients were also tested by 2nd generation recombinant immunoblot assay (RI BA).…”
mentioning
confidence: 51%
“…Previous studies reported variable prevalences of expo sure to hepatitis C virus (HCV) in hemodialysis patients using a 1st generation assay that detects antibodies to a nonstructural protein, clOO-3 [1][2][3]. Circulating anti-cl00-3 is thought to be a sensitive indicator of viremia, as shown by the good correlation with HCV RN A [4], however, its role as a reliable marker of exposure to the virus remains question able.…”
mentioning
confidence: 99%
“…Patients with end-stage renal disease (ESRD) undergoing chronic hemodialysis (HD) are a high-risk group for hepatitis C virus (HCV) infection with a high prevalence of anti-HCV antibodies, as reported by numerous investigators [1, 2, 3, 4, 5, 6, 7, 8, 9, 10]. Time on HD and blood transfusion requirement are the most important risk factors for acquiring HCV in this population.…”
Section: Introductionmentioning
confidence: 99%
“…The observation that hemodialysis patients are a population at risk for HCV, while the staff members show none or poor serological evidence of C infection, suggests that HCV is not so readily transmitted as the hepatitis B virus [2,3], Indeed, the signifi cance of positive antibody test regarding potential infectivity is still controversial, especially in asymptomatic patients detected during screening procedures [4], However, the numerous reports of appreciable amounts of non-transfusion-related HCV seropositivities [1,3] and the increase in prevalence rates with the duration of dialysis [5] suggest the possibility of a cross-infection in the dialysis setting by 'unapparent' parenteral transmission of the virus [6] , To assess the prevalence, incidence and behavior of C infection, we performed a perspective study on a large number of patients dialysed at a single institution; treat ment modalities were therefore uniform. The study was also designed to detect whether the dialysis treatment may be considered a risk factor in contracting the infection.…”
Section: Introductionmentioning
confidence: 99%